2015
DOI: 10.1016/j.mednuc.2015.03.187
|View full text |Cite
|
Sign up to set email alerts
|

Nouveaux indices en TEP/TDM : mythe et réalités

Abstract: Reçu le 8 mars 2015 ; accepté le 12 mars 2015Disponible sur Internet le 7 avril 2015 RésuméLe rôle de l'imagerie multimodalité couplant la tomographie par émission de positons (TEP) et la tomodensitométrie (TDM) est devenu de plus en plus important en oncologie. Son utilisation en routine clinique et dans la majorité des travaux de recherche clinique se limite toutefois à des analyses manuelles et visuelles et par l'utilisation de métriques réductrices, comme le SUV max , qui ne représente qu'un seul voxel de … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 66 publications
(104 reference statements)
0
1
0
Order By: Relevance
“…More recently, a few studies have also focused on extracting features from both the PET and CT components (see the section Promising clinical results below). For a more exhaustive list, we refer the reader to other recent reviews [24, 9, 4549]. From a critical review of these studies, several common issues can be identified.…”
Section: The Present: An Era Of Rapid Expansionmentioning
confidence: 99%
“…More recently, a few studies have also focused on extracting features from both the PET and CT components (see the section Promising clinical results below). For a more exhaustive list, we refer the reader to other recent reviews [24, 9, 4549]. From a critical review of these studies, several common issues can be identified.…”
Section: The Present: An Era Of Rapid Expansionmentioning
confidence: 99%